ANALYSIS OF THE INFLUENCE OF MUSHARAKAH, MUDHARABAH, AND IJARAH FINANCINGS TOWARD PROFITABILITY IN ISLAMIC BANKS (Case Study of Islamic Commercial Banks and Islamic Business Units in Indonesia, Peri - Ageng Cahya Kurnia Putri (EKPI 16 UMY 315, 2016)
The purpose of this study is to examine the relationship between financing in Islamic commercial banks and profitability. Variables used here are Musharakah, Mudharabah, Ijarah and Return on Asset (ROA), examined using cointegration test to find long-run relationship and Vector Error Correction Model (VECM) to find the short-run relationship. Monthly data are collected for the period of January 2012-June 2015. The result shows that there is cointegration (long-run relationship) among Mudharabah, Ijarah and ROA; whereas the VECM estimation shows that ROA is affected positively significantly by Mudharabah. Keywords: Islamic Bank Financing, Financing, Musharakah Financing (MUSY), Mudharabah Financing (MUDH), Ijarah Fianncing, and Return on Asset (ROA).